2013
DOI: 10.3390/en6083692
|View full text |Cite
|
Sign up to set email alerts
|

EMS-Data-Based Load Modeling to Evaluate the Effect of Conservation Voltage Reduction at a National Level

Abstract: This paper proposes a linearized load model to evaluate the effect of conservation voltage reduction at a national level. In this model, the respective active and reactive linearizing parameters for active and reactive loads in a power system are estimated using energy management system (EMS) data resulting from conservation voltage reductions. To verify the validity of the linearized load model, PSS/E simulations were conducted for a test power system. Given that conservation voltage reductions are usually ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Dynamic-load modeling can accurately reflect the load characteristics; however, it requires high time-resolution data. On the other hand, the parameters of static-load modeling can be estimated using SOMAS data because relatively low time-resolution data are sufficient for static-load modeling [32][33][34]. In particular, ZIP (constant impedance, current, and power) load modeling has a simple structure, and its parameters can be derived from just a few data samples.…”
Section: Linearized Load Modeling Based On Somas Data Resulting From mentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic-load modeling can accurately reflect the load characteristics; however, it requires high time-resolution data. On the other hand, the parameters of static-load modeling can be estimated using SOMAS data because relatively low time-resolution data are sufficient for static-load modeling [32][33][34]. In particular, ZIP (constant impedance, current, and power) load modeling has a simple structure, and its parameters can be derived from just a few data samples.…”
Section: Linearized Load Modeling Based On Somas Data Resulting From mentioning
confidence: 99%
“…Given that nationwide CVR is usually in the range 2.0%-5.0%, it is difficult to accurately determine ZIP parameters using SOMAS data obtained from nationwide CVR [34]. Therefore, instead of the ZIP load model, this paper uses a linearized load model, which was proposed in [34] and is described briefly below.…”
Section: Linearized Load Modeling Based On Somas Data Resulting From mentioning
confidence: 99%
“…The effect of load reduction on the generation reduction appears insignificant for this small test case, which is different from the case for bulk power systems. A judgment matrix for the PTDF can be built as shown in Equation (20). …”
Section: Ptdf For the Test Systemmentioning
confidence: 99%
“…It is noteworthy that many utilities have recently evaluated their CVR performance through numerous commissions and strategies as well as the technical and economic benefits of peak demand reduction and energy savings [1][2][3][4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The Pacific Northwest National Laboratory (PNNL) reported that the CVR on a national level in the U.S. can be extrapolated to be 3.04% reduction in annual energy consumption [17].…”
Section: Introductionmentioning
confidence: 99%
“…The aggregation concept may be extended further so that CVR factors determined at the appliance, customer and feeder levels are used to form a CVR factor for the entire network. Other research [4]- [5] has sought to overcome the complexity of extrapolating a deluge of individual load traits to the network level by introducing a linearized approximation to the established definition for CVRp outlined in (1). This paper explores new ways of interpreting load behaviors in the presence of voltage fluctuations, beyond that of established modelling practice, with the intention of assisting the analysis and predictability of network voltage optimization tools, such as CVR.…”
Section: Introductionmentioning
confidence: 99%